MITOCHONDRIAL COI GENE BASED MOLECULAR IDENTIFICATION AND PHYLOGENETIC ANALYSIS IN EXOTIC FISH (OREOCHROMIS MOSSAMBICUS) OF - A. Yaqub; M. Kamran; N. Malkani; K. M. Anjum; M. Faheem; M. Iqbal; R. U. Khan (Journal of Animal and Plant Sciences, 2019)
Tilapia Oreochromis spp. are exotic fish introduced in Pakistan from Malaya in 1951. Due to its omnivorous feeding habits and adaptability to harsh environmental conditions, such as salinity and temperature, is considered suitable for aquaculture in Pakistan. However, to date, classification and phylogenetic relationship among the tilapia cultured in Pakistan are poorly understood. In the present study, samples of tilapia were collected from different aquatic systems of Pakistan and Cytochrome c Oxidase subunit I (COI) of mitochondrial genes were investigated to elucidate molecular characterization and find out phylogenetic relationships. DNA extraction was performed from the fin tissue of collected specimens using modified salt extraction method and COI gene of mtDNA was amplified using universal primers for fish and finally the amplified products were sequenced.  Sequencing results showed that specimens belonged to species O. mossambicus, of family Cichlidae. Sequence analysis was done by the MEGA 7 software, and cladogram were constructed. The sequence analysis of the genes also showed that there was no significant divergence among all the specimen studied. The species of O. mossambicus was not only confirmed but also separated from other species of family Cichlidae with the help of molecular approach using mtCOI sequence.
Keywords: Oreochromis mossambicus; Exotic; COI; mtDNA; molecular identification; phylogenetic analysis